2023
DOI: 10.1186/s12905-023-02188-4
|View full text |Cite
|
Sign up to set email alerts
|

How do carbohydrate quality indices influence on bone mass density in postmenopausal women? A case–control study

Abstract: Background Carbohydrates are the primary energy source in Asian countries, including Iran. An emerging method can be used to measure the quality of carbohydrates, including the carbohydrate quality index (CQI), which includes a variety of components. Low-carbohydrate diet score (LCDS) has been proposed as a new method of scoring micronutrient intake that could provide a reasonable explanation for the link between diet and the risk of chronic diseases. Objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 57 publications
1
1
0
Order By: Relevance
“…In the present study, Ca intake from cake, biscuits and bread contributed to increased osteoporosis risk. These results are consistent with other observations which found that high glycemic index (GI) foods had negative consequences for bone health, including decreased osteoblast activity, increased bone resorption, oxidative stress and inflammation, as well as the induction of acidosis [ 39 , 40 ]. In contrast, complex carbohydrates such as those found in vegetables, legumes and whole grains can increase Ca absorption and neutralize metabolic acid loads in the body [ 9 ].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, Ca intake from cake, biscuits and bread contributed to increased osteoporosis risk. These results are consistent with other observations which found that high glycemic index (GI) foods had negative consequences for bone health, including decreased osteoblast activity, increased bone resorption, oxidative stress and inflammation, as well as the induction of acidosis [ 39 , 40 ]. In contrast, complex carbohydrates such as those found in vegetables, legumes and whole grains can increase Ca absorption and neutralize metabolic acid loads in the body [ 9 ].…”
Section: Discussionsupporting
confidence: 92%
“…2,5 Previous studies have indicated a correlation between dietary habits and BMD. Increased intake of milk, fruits, vegetables, and fish, or a Mediterranean dietary pattern, is associated with a reduced risk of BMD loss, [6][7][8][9] while the opposite is true for high-dose sugar and caffeine intake, or a pro-inflammatory dietary pattern. [10][11][12] However, there is still a lack of research on the relationship between spicy food consumption and BMD.…”
Section: Introductionmentioning
confidence: 99%